Malaria in Britain: Past, present, and future - Kuhn, Katrin Gaardbo (National Academy of Sciences, 2003)
There has been much recent speculation that global warming may allow the reestablishment of malaria transmission in previously endemic areas such as Europe and the United States. In this report we analyze temporal trends in malaria in Britain between 1840 and 1910, to assess the potential for reemergence of the disease. Our results demonstrate that at least 20% of the drop-off in malaria was due to increasing cattle population and decreasing acreages of marsh wetlands. Although both rainfall and average temperature were associated with year-to-year variability in death rates, there was no evidence for any association with the long-term malaria trend. Model simulations for future scenarios in Britain suggest that the change in temperature projected to occur by 2050 is likely to cause a proportional increase in local malaria transmission of 8–14%. The current risk is negligible, as >52,000 imported cases since 1953 have not led to any secondary cases. The projected increase in proportional risk is clearly insufficient to lead to the reestablishment of endemicity.